Administrative and legal actions preceding the canonical erection of new religious house - MICHOWICZ, PRZEMYSŁAW (Prawo Kanoniczne, 2017)
This article, in the rst place, studies the problems concerning the re- ception in the Diocese of a new Institute of Consecrated Life and/or a Society of Apostolic Life. In the process of applying the canonical norms it seems extremely important to choose the right legal instruments in order to act correctly and to accomplish the specic juridical action. Considering the lack of regulation of this atypical procedure in the Code of Canon Law of 1983, the main purpose of this work, was to advance the potential procedure, emphasizing the single steps of legal administrative action issued by the diocesan Bishop. Far from the pretense of exhaustiveness, the purpose is to stimulate the doctrine to elaborate linear administrative procedure for the legal regula- tions of this factispecies and also to manage the discernment parameters, which will minimize every eventuality of failure in decision-making.